Higher education governance and policy change in Western Europe international challenges to historical institutions - Dobbins, Michael 1975-; Knill, Christoph 1965- (Palgrave studies in global higher education, 2014)
This book provides a systematic, comparative analysis of the impact of 'soft Europeanization' on higher education governance in Western Europe. Focusing on the four countries that initiated the Bologna Process -- Italy, France, Germany and the United Kingdom, Michael Dobbins and Christoph Knill explore how the tensions between historical legacies and transnational forces of change have impacted policy pathways. Higher Education Governance and Policy Change in Western Europe tackles the key question of whether or not the Europeanization of the policy field has pushed Western European higher education systems towards a common governance model